2019
DOI: 10.3389/fped.2019.00457
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Mutations (c.883-4_890del and c.1684C>G) of WDR62 Gene Associated With Autosomal Recessive Primary Microcephaly: A Case Report

Abstract: Background: Autosomal recessive primary microcephaly (Microcephaly Primary Hereditary, MCPH) is a rare disorder, affecting 1 in 10,000 children in areas where consanguineous marriages are common. WDR62 gene mutations are the second most common cause of MCPH. Herein, we report a case of primary microcephaly caused by two novel WDR62 mutations, which is, to our knowledge, the first such case report in East Asia.Case presentation: A 6-year-old girl visited our outpatient clinic as a result of microcephaly and del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Our data also supported the notion that WDR62 (MIM# 613583) is the second most frequently mutated gene (14%) of MCPH (Zaqout et al, 2017), because we have found a nearly similar number of MCPH families (15.62%) with mutations in this gene. After a thorough literature review of WDR62 mutations by Poulton and colleagues (Poulton et al, 2014), summarizing a total of 24 mutations, 29 new mutations were published thereafter (Kvarnung et al, 2018; Yi et al, 2019; Zombor et al, 2019). The novel missense mutation reported in our study increased the total number of identified mutations to 54 (Figure 1 and Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also supported the notion that WDR62 (MIM# 613583) is the second most frequently mutated gene (14%) of MCPH (Zaqout et al, 2017), because we have found a nearly similar number of MCPH families (15.62%) with mutations in this gene. After a thorough literature review of WDR62 mutations by Poulton and colleagues (Poulton et al, 2014), summarizing a total of 24 mutations, 29 new mutations were published thereafter (Kvarnung et al, 2018; Yi et al, 2019; Zombor et al, 2019). The novel missense mutation reported in our study increased the total number of identified mutations to 54 (Figure 1 and Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reported cases come from countries that allow marriage between relatives. Complex heterozygotes were found only in 11 cases and their clinical picture did not differ significantly from those in which homozygotes were found [ 6 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 90%
“…Delayed psychomotor development was observed in most children, although in some the motor development was normal in the first months of life [ 28 , 34 ]. Hypotonia was described only in 9 out of 30 [30%] and spasticity or hyperreflexia in 16 out of 44 patients [37%].…”
Section: Discussionmentioning
confidence: 99%
“…Taken individually, 44 out of 60 patients were able to walk independently, and 44 out of 59 patients were able to talk with simple sentences. Objective evaluation of cognitive abilities was only reported for 3 out of 137 patients, for one of whom IQ was assessed using the Korean-Leiter International Performance Scale -Revised test 12 and for two of whom a developmental quotient was calculated from VABS. 1,13…”
Section: Literature Reviewmentioning
confidence: 99%